Red Imported Fire Ant, Solenopsis invicta Buren (Insecta: Hymenoptera: Formicidae: Myrmicinae) - Laura Collins; Rudolph H. Scheffrahn (EDIS)
This document is EENY-195, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2001.